A unique case of oral rehabilitation of a cleft patient without surgical intervention - Ayub, Ayisha; Awais, Ahmad (Hasanuddin University, 2024)
The case presented here elaborates the comprehensive oral rehabilitation treatment protocol followed for a unilateral left cleft lip and palate patient. The patient presented with a class III dental and skeletal relation, missing lateral left incisor, buccally placed canine, left cross bite, inclination of the left central incisor and canine towards the cleft alveolar area along with some other issues. The treatment involved a multidisciplinary approach, including orthodontic treatment, prosthodontics, and restorative dentistry. The case report highlights the successful outcomes achieved without surgery through the coordinated efforts of the dental team.